WORTHY OR NOT? TEACHING ENGLISH TO YOUNG INDONESIAN LEARNERS USING TECHNOLOGY IN THE CLASSROOM - Marselus Suarta Kasmiran (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2020)
Indonesia is one of the seven countries that the principals informed the lack of infrastructure and educational materials. The Indonesian government is improving all aspects of the education. The use of technology in the classroom has been concerned as it is one of the criteria in OECD rank. In this study, we explore the use of technology in the classroom from in-service teachers’ (n = 20, male = 2, female = 18) perspectives. The data were collected with a web-based survey with some open-ended questions which allow the researcher to detect the teachers’ responses. The findings report that some of the teachers use technology to deliver learning and to attract their students. The others may prefer to deliver teaching without technology to make the students experience the real things. Meanwhile, some combine the use of technology and realia to make the students grab the materials easily and to deliver meaningful learning to the students. The study suggests that the government should not only emphasize the improvement in technology and educational infrastructure. The government should also provide training for the teachers which help the teachers to be more creative in using real things around them.